2005
DOI: 10.4103/0973-1482.19589
|View full text |Cite
|
Sign up to set email alerts
|

The optimal use of granulocyte macrophage colony stimulating factor in radiation induced mucositis in head and neck squamous cell carcinoma.

Abstract: GM-CSF reduces the severity of acute side effects of radiation therapy thereby allowing completion of the treatment without interruption. Its remarkable response needs to be evaluated further in large randomized trials. The time of initiation and cessation of GM-CSF during radiation therapy and the required dose needs to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Use of granulocyte/macrophage-colony stimulating factor (GM-CSF) has been used to ameliorate mucositis in cancer patients treated with radiotherapy,63 and to treat chemotherapy-induced neutropenia in many patients treated with chemotherapy 64. Although it is critical for these patients to receive G-CSF/GM-CSF to avoid treatment delays, recent research indicates a potential danger involving the stimulation of tumor angiogenesis by myeloid cells.…”
Section: Clinical Importance and Implicationsmentioning
confidence: 99%
“…Use of granulocyte/macrophage-colony stimulating factor (GM-CSF) has been used to ameliorate mucositis in cancer patients treated with radiotherapy,63 and to treat chemotherapy-induced neutropenia in many patients treated with chemotherapy 64. Although it is critical for these patients to receive G-CSF/GM-CSF to avoid treatment delays, recent research indicates a potential danger involving the stimulation of tumor angiogenesis by myeloid cells.…”
Section: Clinical Importance and Implicationsmentioning
confidence: 99%
“…However, this study was not randomized and there was no placebo or treatment control group. Several other studies have since supported this finding and some even suggested that GM-CSF is more useful in patients receiving hyperfraction RT [1,67,68]. A more recent study using a higher subcutaneous dose of 4 μg/kg/day suggested that GM-CSF is more effective than conventional treatment in severe mucositis [69].…”
Section: G-csf/cm-csfmentioning
confidence: 76%
“…Radiation therapy (RT) is an important and indispensable mode of treatment for head and neck cancers, with up to 75% of all head and neck cancer patients receiving it [1]. As it is currently not possible to prevent radiation therapyinduced mucositis (RM) from happening, most healthcare workers aim to at least provide symptomatic relief to alleviate patients' suffering.…”
Section: Introductionmentioning
confidence: 99%
“…No intraoral tumor ablative procedures that altered the mucosal surfaces were carried out. 11 All the procedures were performed in accordance with the hospital's ethical guidelines.…”
Section: Patient Selection and Characteristicsmentioning
confidence: 99%